Activation of forkhead box O3a by mono(2‐ethylhexyl)phthalate and its role in protection against mono(2‐ethylhexyl)phthalate‐induced oxidative stress and apoptosis in human cardiomyocytes. Issue 4 (8th October 2020) - Wang, Zeze; Liu, Yi; Liu, Xuehui; Zhou, Lixiao; Ma, Xindi; Liu, Junyao; Wang, Lei; Guo, Huicai
Abstract: Mono(2‐ethylhexyl)phthalate (MEHP), the active metabolite of di(2‐ethylhexyl)phthalate (DEHP), is known to exert cardiotoxicity. The aim of the present study was to investigate the role of forkhead box O3a (FOXO3a) in MEHP‐induced human AC16 cardiomyocyte injuries. MEHP reduced cell viability and mitochondrial membrane potential (ΔΨm), whereas it increased lactate dehydrogenase (LDH) leakage, production of reactive oxygen species (ROS), and apoptosis in cardiomyocytes. The expression of FOXO3a and its target genes, mitochondrial superoxide dismutase (Mn‐SOD) and apoptosis repressor with caspase recruitment domain (ARC), increased after MEHP exposure, but the expression of p‐FOXO3a protein was decreased. Overexpression of FOXO3a decreased the production of ROS and the apoptosis rate induced by MEHP, and the expression of Mn‐SOD and ARC was further increased after MEHP exposure. In contrast, knockdown of FOXO3a resulted in increased ROS production and apoptosis and suppressed the expression of Mn‐SOD and ARC in the presence of MEHP. However, overexpression or knockdown of FOXO3a did not affect MEHP‐induced loss of ΔΨm. In conclusion, the loss of ΔΨm and apoptosis are involved in MEHP‐induced cardiomyocyte toxicity. Activation of FOXO3a defends against MEHP‐induced oxidative stress and apoptosis by upregulating the expression of Mn‐SOD and ARC in AC16 cardiomyocytes. Abstract : The expression of FOXO3a in AC16 cardiomyocytes increased after MEHP exposure. Overexpression of FOXO3a decreased the production of ROS and the apoptosis induced by MEHP, and the expression of Mn‐SOD and ARC was further increased after MEHP exposure. Knockdown of FOXO3a resulted in increased ROS production and apoptosis and suppressed the expression of Mn‐SOD and ARC after MEHP exposure. In conclusion, activation of FOXO3a defends against MEHP‐induced oxidative stress and apoptosis by upregulating the expression of Mn‐SOD and ARC.